Effect of liquid scrubber’s flowrate and residence time on efficiency of ammonia gas removal: article - Abd Samat, Muhammad Hafizuddin; Zainal, Safari (2018)
Ammonia gas is an alkali gas which can causes various effects towards living organisms if these strong alkali gases are release to the environment without treated properly. The objectives of this research are to study the effect of flowrate and residence time on efficiency of ammonia gas removal. An optimum flowrate of inlet gases and the residence time for the reaction which is absorption process are essential or very important in conducting the contaminant gases absorption process because it will affect the efficiency of the alkali gas removal or the percentage of the alkali gas that have been absorbed. In this research, the analysis was conducted to study the efficiency of the ammonia gas removal by using different flowrate and residence time. The relationship or effect of the flow rate and residence time is shows in the graph. In this research the flowrate that were used is 1ml/min, 2ml/min, 3ml/min, 4ml/min and 5ml/min and the residence time are varies 2min, 4min, 6min, 8min and 10min. The ammonia is transfer into the scrubber with contain 200ml each solution at every experiment respectively. Therefore, based on this research the most efficiency ammonia gas removal that have been tested was determined and record for treatment of ammonia.